Top 100 Cited Articles on Clinical Hematopoietic Stem Cell Transplantation: A Bibliometric Analysis - Shahzad, Moazzam; Chaudhary, Sibgha Gull; Anwar, Iqra; Arslan, Muhammad; Naseem, Zehra; Fatima, Naira T.; Abbas, Sakina; Ali, Tayyaba; Siddiqui, Raheel S.; Hematti, Peiman; Abhyankar, Sunil H.; McGuirk, Joseph P.; et al. (Frontiers in Medicine, 2022)
We conducted a bibliometric analysis to identify scholarly impact and factors associated with the top 100 cited articles on clinical hematopoietic stem cell transplantation (HSCT). In January 2021, a title-specific search was conducted. Non-HSCT and pre-clinical (in-vitro and animal) studies were excluded. A total of 39,406 records were identified and a list of the top 100 articles was made. Articles included in our study were characterized by the citations received, publication year, topic, study design, authors, h-index, and institutions. Linear regression analyses were performed. The 100 most cited articles were published over 52 years from 1968 to 2020, with a maximum number of articles (n = 40) published in the 1990s decade. Top-100 articles were cited 62,002 times with a median citation count of 465 (range 336–2240). The top-cited articles originated from 12 countries. United States contributed 69 articles. The University of Washington Fred Hutchinson Cancer Center (n = 15) was the leading institution. Blood (n = 32) and New England Journal of Medicine (n = 31) made the greatest contribution, and 52 manuscripts were clinical trials. The first author's H-index significantly correlated with citation count while journal impact factor, years since publication, first author's gender, and the number of authors did not have a significant association with the number of citations. In a multivariate regression model, the first author's h-index (regression coefficient 5.46, 95% confidence interval 2.99 to 7.93, p < 0.001) independently correlated with the citation count. Our study highlights the most influential articles on clinical HSCT and provides valuable insight for future research needs of the specialty.